Is Maternal Breastfeeding Motivation and Exclusive Breastfeeding Influenced by early Marriage age? - Pitaloka, Arditya Dyah Ayu; Nurhayati, Eka; Hadi, Hamam; Lee, Katherine; Paramashanti, Bunga Astria (Journal of Nepal Paediatric Society, 2022)
Introduction: Exclusive breastfeeding is beneficial for mother and child health. However, exclusive breastfeeding rate is low among young mothers. Thus, our study aimed to examine the relationship between maternal breastfeeding motivation and exclusive breastfeeding and determine whether the early marriage age influences both variables in Gunung Kidul District, Yogyakarta Special Region, Indonesia. Methods: A cross-sectional design was conducted among young adolescent mothers. A total of 144 married women who had young children aged six to 12 months were selected using simple random sampling. Exclusive breastfeeding was the dependent variable, while maternal breastfeeding motivation was the independent variable. Descriptive statistics, chi-square test, multiple logistic regression, and mantel haenzel tests were performed to analyse the relationship between variables using STATA 14.2. Results: Maternal age at marriage > 20 years (OR = 2.98; 95%CI: 1.15-7.74) and good maternal breastfeeding motivation (OR = 22.02; 95%CI: 7.55-64.2) were associated with exclusive breastfeeding practice. In the stratification analysis, a larger association was found between maternal breastfeeding motivation and exclusive breastfeeding among younger mothers (OR=3.96; 95%CI: 2.25-6.97) compared to older mothers (OR = 1.79; 95%CI: 1.29-2.48). Conclusions: Maternal breastfeeding motivation positively influences exclusive breastfeeding practice. Notably, young mothers are more likely to be motivated to breastfeed their children exclusively than older mothers. The results suggest a need to improve maternal breastfeeding motivation through quality prenatal and postnatal care services that involve other family members.